Making sense in asset markets: Strategies for implicit organizations - Johannes M. Lehner (Cogent Economics & Finance, 2015)
While asset markets are traditionally left to economic inquiry, the paper shows that there is both a legal possibility and an incentive for organizing within such markets and for exercising market share-based strategic maneuvering. It proposes, based on sensemaking theory, Implicit Organizations in asset markets to exploit equivocality for momentum trading strategies. An Implicit Organization fulfills the criteria of an organization, while maintaining the image of a perfect market. Its members coordinate via market signals and fixed investment time windows to ensure positive returns to strategic maneuvering in asset markets. In support of hypotheses derived from sensemaking theory, results of empirical studies from two different investment contexts (Xetra and NYSE) provide evidence that equivocal analysts' recommendations predict investment returns after a fixed time period.
Keywords: L22; G12; 330; asset markets; coordination; equivocality; organization; sensemaking; signaling